Epidermal p65/NF‐κB signalling is essential for skin carcinogenesis. Issue 7 (21st June 2014) - Kim, Chun; Pasparakis, Manolis
<x xml:space="preserve">Abstract</x> p65‐dependent NF‐κB signalling in keratinocytes promotes DMBA‐/TPA‐induced skin carcinogenesis by protecting them from DNA damage‐induced death. <boxed-text content-type="graphic" id="emmm201303541-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text>